THE IMPORTANCE OF DEVELOPING CRITICAL THINKING SKILLS OF PRIMARY SCHOOL STUDENTS IN A MODERN EDUCATIONAL ENVIRONMENT (International Conference on Education, Psychology and Humanities, 2026)
This article highlights the theoretical and practical significance of developing critical thinking skills among primary school students in a digital educational environment. It analyzes the issues of fostering students’ independent thinking, information analysis, comparison, conclusion-making, and rational approaches to problem-solving through educational processes organized on the basis of digital technologies. Furthermore, the article emphasizes interactive teaching methods, digital platforms, multimedia tools, and teachers’ pedagogical competence as key factors in developing critical thinking in primary education. Along with the advantages of the digital learning environment, the necessary pedagogical conditions for its effective implementation are also discussed.
Keywords: Digital educational environment, critical thinking, primary education, interactive methods, information analysis, independent thinking, digital technologies, pedagogical approach, media literacy, educational effectiveness.